Development of Automatic Load-Shedding Strategy for Stand-Alone Photovoltaic System - Mohd Nasir, Mohamad Na'im; Mohd Farith, Mashitah; Jamri , Mohd Saifuzam; Jali, Mohd Hafiz; Jaafar, Hazriq Izzuan; Sulaima, Mohamad Fani (2014)
Nowadays, the use of solar energy are extremely developed and delivered worldwide. This paper presents the development of automatic load-shedding strategy for stand-alone photovoltaic system. The design of this project shows the characteristics of solar energy and operation of load-shedding strategy. The main objective of this project is to implement the load-shedding strategy as an emergency controller for stand-alone photovoltaic system. To achieve the objective, research of basic understanding related to this project is very important to understand more about the characteristics of each element in this project. The circuit of the load-shedding system is designed in the SoftCad Eagle PCB Design software. The algorithm controlling the load-shedding scheme is developed in the Arduino IDE. Then, the coding programmed is burn in the microcontroller board and installed with the hardware. Output of this project can support the DC loads and load-shedding strategy scheme is performed based on the designed algorithm.